Design and motion analysis of multi-motion mode pipeline robot. Issue 1 (1st April 2022) - Yan, Feng; Gao, Haitao; Zhang, Lei; Han, Yali
Abstract: Aiming to improve the adaptability level of single motion form pipeline robots, a wheeled pipeline robot with multiple motion modes is designed. The overall scheme of the pipeline robot is given. The self-adaptive diameter-changing mechanism, wheel displacement mechanism, and turning mechanism are designed. The motion and mechanical models of pipeline robots during travelling are established; on this basis, the robot's main body structure is optimised.